Pengaruh Kesiapan Belajar terhadap Prestasi Belajar Menulis Cerita Pendek dalam Mata Pelajaran Bahasa Indonesia - Sriwahyuni, Sriwahyuni; Nazirun, Nazirun (UIR Press, 2024)
Readiness is essentially a quality or strength that enables an individual to respond in a certain way. Readiness also plays a significant role in the learning process as it can result in positive outcomes in achieving learning goals and enhancing the efficiency and effectiveness of learning. The learning outcomes obtained by students may vary, influenced by various factors. One of the significant factors is readiness for learning, as stated by Slameto (2003:59), who suggests that a student's learning success will be optimal if there is readiness within them. This study aims to investigate the Influence of Learning Readiness on Learning Outcomes in Indonesian Language for Grade XI AKL Students at SMK YABRI Integrated Pekanbaru. In this study, there are two variables, namely the Independent Variable (X) Learning Readiness and the Dependent Variable (Y) Learning Outcomes. This research employs a Quantitative Approach. The hypothesis of this study is Ha: there is a significant influence between learning readiness and learning outcomes for Grade XI AKL students at SMK YABRI Integrated Pekanbaru. Data were collected through a questionnaire consisting of 71 items with a scale of 1-5, with a score range for the learning readiness instrument of 30-150. The analysis results show that the average score (mean) is 114.7, with a standard deviation of 58.42. These scores indicate that students' readiness for learning tends to be low. As for learning outcomes, the score range is 0-100, with an average score of 70.07 and a standard deviation of 10.064. These scores indicate that students' learning outcomes also tend to be low.